ROLA ORZECZNICTWA SĄDU NAJWYŻSZEGO W ZAKRESIE PROBLEMÓW PRAKTYCZNYCH ZWIĄZANYCH Z URLOPEM NA ŻĄDANIE - Gajda, Mateusz (Zeszyty Prawnicze, 2016)
The Jurisdiction of the Polish Supreme Court in the Scope of Practical Problems Connected with Leave on Request Summary The article discusses the role of the jurisdiction of the Polish Supreme Court in the scope of practical problems connected with leave on request. Ever since its introduction in the Polish Labour Code, this institution has been generating misgivings and reservations both as regards the case law and the doctrine. The role of the Supreme Court in connection with this regulation is significant due to the legislator’s lack of precision. Verdicts handed down by the Supreme Court on these issues have in general been changing the legal character of the institution by emphasising the organisational function of labour law. The interpretation of these legal provisions proposed by the Supreme Court has clarified some of the rights and duties of parties in matters connected with leave on request. Despite this, there are still situations where the current wording of the provisions may lead to disputes between employee and employer. Therefore, the current provisions of the Labour Code within this scope require amendment.